THE EFFECT OF WILLING TO PAY TAXES AND THE LEVEL OF UNDERSTANDING OF TAXPAYERS ON TAX COMPLIANCE - Tri Widyastuti Ningsih (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
The aims of this research are for knowing : 1). The influence of tax payment willingness toward tax payment obedience in reclame of tax in Badan Pendapatan Daerah (Bapenda) Semarang. 2). The Influence of tax obligatory understanding toward tax payment obedience in reclame of tax in Badan Pendapatan Daerah (Bapenda) Semarang). The data used in this research is primary data, which tehe data source is obtained from questionnaire. The population in this research is the reclame execution of tax obligatory registered in Bapenda Kota Semarang Th 2017-2018. The sample in this research is 100 tax obligatory reclames, by using slovin method as the sample collection technique. The research findings show that 1). Tax payment willingnes (X1) has positive influence and significance on tax payment obedience (Y) with significance result 0.000 score lesser than 0.05, so the hypothesis tax payment willingnes (X1) is accepted (Ho1 is rejected and Ha1 is accepted). 2). The level of tax obligatory understanding (X2) has positive influence and significance on tax payment obedience (Y) with the significance result 0.007 score lesser than 0.05, so the pypothesis the level of tax obligatory understanding (X2) is accepted (Ho2 is rejected and Ha2 is accepted).